Capacity building of stakeholders in Niger Office on seed production of drought tolerant rice varieties and system of rice intensification in Mali - Sidibe, M; Keita, B.; Dossou-Yovo, E.R. (2025)
This report presents the outcomes of capacity building activities implemented under the AICCRA project in the Niger Office, the largest irrigation scheme in Mali contributing 40% of national rice production. The training program focused on building the technical capacity of extension agents, local NGOs, women-led organizations, and farmer leaders in the production of drought-tolerant rice seeds and the application of the System of Rice Intensification (SRI) as a climate-smart agricultural innovation. A total of 1,080 participants (899 men and 181 women) were trained through a combination of farmer field schools, indoor workshops, mutual learning groups, and mass communication campaigns. These sessions aimed to enhance seed quality assurance, improve water-use efficiency, strengthen climate resilience, and promote gender-inclusive leadership in rice value chains. The trainings contributed to significant progress towards adoption targets, with over 65,196 stakeholders sensitized and 22,280 farmers trained in climate-resilient practices, exceeding dissemination targets. The outcomes demonstrate a strong foundation for large-scale scaling of drought-tolerant rice technologies and intensive rice cultivation systems to improve productivity and resilience in Mali’s rice sector.